Prevalence, patterns and determinants of unmet needs of contraception among married women in Imphal East district of Manipur: a cross-sectional study - Rajkumari, Bishwalata; Maisnam, Annie Bichal; Devi, Oinam Gunipriya; Yumnam, Rajshri (International Journal Of Community Medicine And Public Health, 2024)
Background: In many countries, unmet need for family planning among pregnant women is a main reason of closely spaced births, child bearing at a very early age, unsafe abortions or physical abuse, all of which are considered as main co-factors to high maternal and infant mortality. Understanding the unmet need of contraception and contraceptive behaviour among married women will help in enhancing the service provision among them. The study was done with the objective to estimate the prevalence of unmet need of contraception and patterns of contraceptive usage among currently married women and to determine the association between unmet need of contraception and some selected variables. Methods: A cross-sectional study was conducted using pre-tested, semi-structured questionnaire among currently married women. Bivariate and multivariate logistic regression analyses were used to identify factors associated with the unmet need of contraception. A p value of <0.05 was taken as statistically significant. Results: Out of 300 respondents, more than half (165, 55.0%) had unmet needs of contraception. Age of the participant AOR=1.057 (1.013-1.103), self-employed AOR=0.433 (0.222-0.844), pregnant at present AOR = 7.693 (2.868-20.635), discussing about FP with husband AOR=0.534 (0.305-0.936) and those ever received FP services AOR=2.794 (1.579-4.944) were significantly associated with unmet need of contraception. Conclusions: Five out of ten women were found to have unmet need for contraception. Awareness programs regarding importance of family planning and various family planning services available at health facilities should be conducted from time to time among the public.